The Education on the Prevention of the Spread of the Covid-19 by Provisions of Handwashing Facilities and Masks - Meda Canti; Anastasia Tatik Hartanti (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The covid-19 is an infectious disease caused by the coronavirus, which has become a pandemic worldwide, including Indonesia. One of the red zones of positive cases is Bogor Regency, with its case counts consistently increasing every day. To prevent the spread of the covid-19, education and provision of facilities are therefore needed. This community service activity aimed to educate and instill awareness among the residents, peddlers, online motorcycle taxi drivers, and cleaners about preventing the spread of the covid-19 through handwashing facilities and masks. The community service activity was carried out in RW 13, Padasuka Village, Ciomas District, Bogor Regency. This activity began with the placement of posters in strategic locations and direct instructions on preventing the covid-19. In addition, 100 masks were distributed to the residents, peddlers, online motorcycle taxi drivers, and cleaners who were still actively working in RW 13, Ciomas District. Ten handwashing facilities were also provided in strategic locations. The results showed that the counseling and mentoring managed to nurture the residents' awareness to wash hands and wear masks correctly. The monitoring process also indicated that residents were becoming increasingly concerned about maintaining cleanliness and wearing masks correctly when doing outdoor activities. This service activity fostered new habits of the residents, peddlers, online motorcycle taxi drivers, and cleaners to wash their hands properly and wear masks during the pandemic.